The comparative study of side effect DMPA with OCP (LD) in reproductive women referring to health center in Kalaleh - M Mirmohammadali; T Mirmolaei; Gh Babaei; N Borghei (Tehran University of Medical Sciences, 2002)
This is a retrospective research in order to compare the side effect of DMPA with OCP in reproductive women referring to health center in Kalaleh in year 1998. In this assessment the total number of women participated were 198, from this 115 were using Depo medroxy progesterone injection, and 83 women taking OCP. All the research subjects were assessed for having specifice character necessary for this research, and participated willingly. Data collecting was done by the means of questionnaire and checklist, data analysis was performed. The result revealed most users of DMPA were older with higher incidence of pregnancy and more children, lower socio - economical education and using injection for shorter period, comparing to women taking tablets, however the users of injection were taking OCP before, but those taking OCP never used any other method of contraceptive. There was a significant differences in headache, nausea, decreased vaginal discharge and menstrual problems, but no significant differences in acne, backache, leg cramps, mastalgia and hair loss were observed.